Estimation of Total Carbon Stock and Mangrove Health Index in Sidoarjo using Machine Learning Spectral Analysis Method of Sentinel-2A Satellite Imagery - Alina, Aldea Noor; Yahya, Fahrul; Safitri, Dika Ayu; Sanjaya, Hartanto; Rahmawaty, Mitha Asyita (GEOID, 2025)
The mangrove ecosystem has the potential ability to absorb carbon dioxide better than other forest ecosystems. It is noted that mangrove forests have an important role in reducing the concentration of carbon dioxide in the air. Changes in land cover conditions, massive development of urban areas, and the large need for housing in the Sidoarjo are the main causes of the decline in the area of mangrove forests which have been converted into fish ponds and residential areas. This triggers a decline in the quality of mangroves and will directly impact on reducing the capacity to store carbon reserves in Sidoarjo Regency. Biomass estimation calculations were carried out using the NDVI algorithm from remote sensing results using Sentinel Imagery – 2A. Apart from that, the mangrove health index was also calculated using the GCI (Green Chlorophyll Index), SIPI (Structure Insensitive Pigment Index), NBR (Normalized Burn Ratio), and ARVI (Atmospherically Resistant Vegetation Index). Based on the calculation results, the value obtained for the coastal area of Sidoarjo Regency the TCS or total carbon stock ranged from 1.1679468503445e-09 to 84.3344 TonC/hectares. Meanwhile, the results of the mangrove health index calculation show that the condition of mangroves in the coastal area of Sidoarjo Regency has a sufficient mangrove health index, with the highest area being 637.77 hectares, while only 10.80 hectares are available has a good health index. The results of this study are expected to be one of the bases for decision-making and policies in the rehabilitation and conservation of mangrove in Sidoarjo.